Development of a process reference model for construction supply chains: the contractor's view - Stamatiou, Dimitrios-Robert (Σχολή Μηχανολόγων Μηχανικών, 2018)
The construction industry has been described by its clients as ineffective and lacking innovation. There have been many studies aiming to identify the causes of these problems and to provide applicable solutions. One of the proposed solutions is the adoption of supply chain management principles by all actors in the industry (clients, contractors, subcontractors, etc.). Supply chain management in the construction industry has been studied over the past twenty years, and once debates on its applicability in the industry were settled, research took off. Construction supply chain management is a novel research field and construction practitioners are not informed about the progress made in academia. The focus of this dissertation is on contractors as they have direct contact with the client. Clients in the in the construction industry have a huge impact on the end product as they set the requirements for each project. Contractors cannot afford to cover all client requirements internally and turn to subcontractors and material/service suppliers to cover this gap. This makes contractors the most important link in a project’s supply chain. Construction practitioners in contractor organisations are aware of the concept of processes as it is part of their daily routine. This provides fertile ground for the description of the contractors’ supply chain through a process view. The aim of this dissertation is to provide a process reference model for construction supply chains focussing on the contractor. In order to achieve this, a demanding but straightforward methodology is employed. A literature review identifying the characteristics and particularities of the industry, defining the concept of construction supply chain management and analysing previous studies is performed. This provides the background for the creation of the process reference model. Next, an existing supply chain management process reference model is selected to provide the backbone of the model proposed. This model is adapted to the construction industry based on the results of the literature review. A process modelling tool that can depict multiple views of supply chain processes is selected to support the modelling effort. The literature is studied further in order to create a process reference model that considers as many aspects of the construction supply chain as possible. These aspects are grouped into nine functions: determine supply chain management strategies, client relationship management, new project development, supplier relationship management, develop key performance indicator framework, demand management, work package management, construction flow management, and claims management. Each of these functions contains a number of strategic and operational processes. These processes are based on best practices identified in the literature and are validated and enriched with undocumented best practices through semi-structured interviews with experienced senior staff of both SME contractors and large contractors. This ensures that the model can be implemented by most contractors in the industry. Furthermore, the analysis of the interviews provides insights to the differences in supply chain management practices of the different sized contractors. The value of the proposed model lies in the fact that it not only describes construction supply chain management functions and processes at a high level, but it also describes the requirements for its adoption and implementation. It can prove useful for both academics and practitioners. It provides academics with a tool to integrate the provided processes with other supply chain views such as risk management or decision support systems. Practitioners can benefit from the specific characteristics of the model (structure, verbal and diagrammatic descriptions, developed in free software) in order to improve, benchmark and compare the performance of specific project supply chains or the performance of their entire supply chain practices and strategies.